# Give an equation for c not involving a.?

Combine c=4a-3 and 2b=3a-8

### 8 Answers

- PinkgreenLv 71 month ago
c=4a-3--------(1)

2b=3a-8--------(2)

3(1)-4(2)

=>

3c-8b=-9+32

=>

3c=23+8b

=>

c=(23+8b)/3

- PhilipLv 61 month ago
c=4a-3...(1), 2b=3a-8...(2).;

(2)---> a = (1/3)2(b+4) = (2/3)(b+4).;

Then (1)---> c = 4[(2/3)(b+4)] -3 = (8/3)b +(32/3) -(96/3) = (8/3)b -(64/3) = (8/3)(b-8);

ie., c = (8/3)(b-8).

- KrishnamurthyLv 71 month ago
An equation for c not involving a.

Combine c = 4a - 3 and 2b = 3a - 8

a = (c + 3)/4

- How do you think about the answers? You can sign in to vote the answer.
- JeremyLv 61 month ago
1)

c = 4a - 3 ===> c + 3 = 4a ===> a = (c + 3)/4.

2)

2b = 3a - 8 ===> 2b + 8 = 3a ===> a = (2b + 8)/3.

3)

If "a = (c + 3)/4" and "a = (2b + 8)/3", therefore:

(c + 3)/4 = (2b + 8)/3.

3 * (c + 3) = 4 * (2b + 8).

3 * c + 3 * 3 = 4 * 2b + 4 * 8.

3c + 9 = 8b + 32.

3c = 8b + 32 - 9.

3c = 8b + 23.

c = (8b + 23)/3 <=== ANSWER.

Or, alternatively: c = (8/3) * b + 23/3.

- Wayne DeguManLv 71 month ago
c = 4a - 3 and 2b = 3a - 8

The second equation can be re-arranged to make a the subject

so, 3a = 2b + 8

Hence, a = (2b + 8)/3

Putting this into the first equation for a gives:

c = 4(2b + 8)/3 - 3

or, c = 8b/3 + 32/3 - 9/3

so, c = 8b/3 + 23/3

Then, c = (8b + 23)/3....which gives c in terms of b

:)>

- llafferLv 71 month ago
If you want to remove the "a", then solve one equation for "a" in terms of the other variable and substitute into the other equation. This will give you a new equation with two unknowns, "b" and "c". Then you can solve for c.

So we have:

c = 4a - 3 and 2b = 3a - 8

The first is already c in terms of a, so we want to leave that alone for now. Solve the other one for a in terms of b:

2b = 3a - 8

2b + 8 = 3a

(2b + 8) / 3 = a

Now we can substitue that expression for "a" in the other equation:

c = 4a - 3

c = 4(2b + 8) / 3 - 3

Let's distribute the 4 and get a common denominator so we can simplify this:

c = (8b + 32) / 3 - 9 / 3

Now we can subtract the numerators:

c = (8b + 32 - 9) / 3

and simplify:

c = (8b + 23) / 3

or:

c = (8/3)b + 23/3

Either gives you c in terms of b.